Biographies of the most famous scholars of the city of Jor during the Abbasid era (132 -656 AH) (Journal of the College of Basic Education, 2024)
The research focused on studying the biographies of the most famous scholars of the city of Jor during the Abbasid era (132-656 AH), as many of them emerged who took it upon themselves to spread Islamic culture in the city and other cities of the Islamic East. Some of them moved to Baghdad, the capital of the Abbasid Caliphate, and others moved to Kufa, Basra, and other countries. The Levant, Egypt, Mecca, Medina, and other Arab and Islamic cities. Among the most prominent scholars of the city of Jur during the Abbasid era were: Sallam bin Janada bin Sallam Al-Juri (d. 245 AH), the hadith narrator and narrator who was the trustworthy of his time, and Muhammad bin Ibrahim bin Imran Al-Juri (d. 359 AH), who was one of Writers and a scholar in the knowledge of genealogy and the sciences of the Qur’an, and Ahmed bin Salam bin Khalid Al-Juri, (d. 360 AH), who served as the judge of the city of Jour and was a narrator and hadith narrator, and other scholars who specialized in various sciences such as grammar, literature, poetry, and so on.